Effects of LGBT Nursing Education Using Simulation - Sook Jung Kang; Hye Young Min (Korean Society of Women Health Nursing, 2019)
PURPOSE: As health care needs for Lesbian, Gay, Bisexual and Transgender (LGBT) are becoming increasingly important, it has become imperative for the nurses to be attentive towards their health problems and provide nursing care with an open-minded attitude. Due to limited opportunity to provide direct nursing care to LGBT patients, it is hypothesized that simulation would provide good opportunity for students to experience LGBT nursing care in a safe environment. This study was conducted to develop and apply simulation of LGBT nursing care to ultimately provide unbiased nursing care for LGBT population and prepare basic data for LGBT nursing education. METHODS: This study was a single-group pre-post experimental design study for 57 senior nursing students based on the comparison of existing LGBT knowledge, general attitude towards LGBT, and nursing attitude towards LGBT before and after simulation. The scenario content included discussion of coming out issue, providing sexual health information, and supportive nursing care for LGBT population. Data were analyzed with descriptive statistics and Wilcoxon signed rank. RESULTS: Simulation education-led to a significant increase in LGBT knowledge and nursing attitude. However, there was no change in the general attitude towards LGBT. CONCLUSION: The results of this study suggest that LGBT education using simulation may be effective for nursing students and nurses from the point of concern for LGBT population. It is hypothesized that future LGBT educational programs might need more detailed information from both care recipients and nurses. Finally, LGBT education needs to be included in the nursing education curriculum.